Towards Positing a Paradigm for Continuous and Comprehensive Evaluation in Social Sciences - Mandal, Pratyusa Kumar (JOURNAL OF INDIAN EDUCATION, 2010)
The present article is an endeavour to raise a few important points concerning evaluation in social sciences, which are often overlooked by boards and educational institutions while conceiving and designing a school-based scheme of continuous and comprehensive evaluation. There is no doubt that social sciences have generally been on the receiving end of the casual and apathetic attitude of educational planners and administrators in the country. The situation might get worse if it is further neglected under the new scheme of evaluation. As is well-known, any scheme of evaluation should to be tailored to the rigours and demands of a discipline rather than giving it a short shrift. There is a genuine concern that this may actually turn out be so. Therefore, it is all the more necessary that the points raised in the present article are taken note of and widely debated.